Stad-Type Cooperative Learning Model with Talking Stick to Increase Learning Outcomes in Object Composing Particle Material - Hasmirah, Hasmirah (International Journal of Management and Education in Human Development, 2021)
This study aims to improve product learning outcomes and social skills of class IX students on the material constituent particles through the application of a combination of STAD type cooperative learning model with talking stick MTsN 2 Kendari. This research was conducted in the even semester of the 2019/2020 school year, at SMP MTsN 2 Kendari in class IX students totaling 21 students consisting of 11 male students and 10 female students. Factors observed in this study were student factors and teacher factors. This research was carried out in 2 (two) cycles, including: a) planning; b) implementation of actions; c) observation and evaluation; d) reflection. The data obtained in this study were analyzed using descriptive statistics which are intended to provide an overview of improving student learning outcomes who are taught through the application of the STAD type cooperative learning model with talking stick. The results showed that through the application of a combination of STAD type cooperative learning model with talking stick can increase student and teacher activity where in the first cycle the average student activity was 3.4 (Slightly Good) then after learning was carried out in the second cycle the average student activity increased to 3 ,8 (good) and the average teacher activity in the first cycle is 3.2 (good enough) then after the second cycle is carried out it becomes 3.8 (good). Through the application of the STAD type cooperative learning model with talking stick it can improve student learning outcomes on the material constituent particles where the average student learning outcomes in the first cycle are 71.42 with the percentage of student learning completeness that is 71.42% and after the evaluation is carried out in the second cycle then the average student learning outcomes become 78.09 with a percentage of student learning completeness of 90.47% so that the Minimum Completeness Criteria for schools, namely at least 75% of students obtaining a score of 70 can be achieved.